2010
DOI: 10.1007/s11814-010-0169-8
|View full text |Cite
|
Sign up to set email alerts
|

Parameter effect on photocatalytic degradation of phenol using TiO2-P25/activated carbon (AC)

Abstract: P25 powder embedded and TiO 2 immobilized on activated carbon (TiO 2 -P25/AC) was prepared by P25 powder modified sol-gel and dip-coated method. The photocatalysts were characterized by XRD, BET, SEM and their photocatalytic activities were evaluated through phenol degradation in a fluidized bed photoreactor. The addition of P25 in the photocatalysts could significantly enhance the photocatalytic activity, and the optimum loading of P25 was 3 g L −1 . The operating parameter results indicated that the optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(29 citation statements)
references
References 55 publications
4
25
0
Order By: Relevance
“…Generally, heat treatment at high temperature could induce the crystallinity and phase transition of metal oxides. 36,37 In this case, only increase in crystallinity was observed as the temperature used for each cycle was 100 C. FESEM was used to analyse the surface morphology and porosity of TiO 2 NPs aer ten recycles. Fig.…”
Section: Xps Analysismentioning
confidence: 99%
“…Generally, heat treatment at high temperature could induce the crystallinity and phase transition of metal oxides. 36,37 In this case, only increase in crystallinity was observed as the temperature used for each cycle was 100 C. FESEM was used to analyse the surface morphology and porosity of TiO 2 NPs aer ten recycles. Fig.…”
Section: Xps Analysismentioning
confidence: 99%
“…Hence, it has rather great potential for the field application. Another point to be noted is that the photodegradation performance of immobilized titania might be enhanced by giving certain treatments, like aeration, pH adjustment, and controlling catalyst loading [1,43]. For example, an aeration treatment will provide a better mixing condition for the photocatalytic system, hence more contact between immobilized catalyst and the pollutants will likely occur [43].…”
Section: Photodegradation Performance Testmentioning
confidence: 99%
“…Another point to be noted is that the photodegradation performance of immobilized titania might be enhanced by giving certain treatments, like aeration, pH adjustment, and controlling catalyst loading [1,43]. For example, an aeration treatment will provide a better mixing condition for the photocatalytic system, hence more contact between immobilized catalyst and the pollutants will likely occur [43]. In addition, it might supply sufficient amount of dissolved oxygen needed for the photodegradation reaction, thus increasing the photocatalytic activity of immobilized titania [43].…”
Section: Photodegradation Performance Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Lam et al (2010) indicated similar results, and photons do not reach the surface of photocatalyst to activate it to generate hydroxyl radicals. Due to that, initial concentration range of 100 µg/L to 150 µg/L was chosen in order to determine the optimum value of the photocatalytic treatment process.…”
Section: Effect Of Initial Concentrationmentioning
confidence: 54%